Bringing nature back: using hibernation to reboot organ preservation. (1st November 2018) - Hadj‐Moussa, Hanane; Storey, Kenneth B.
Abstract : Recently, organ transplant therapy has received a major boost from a change in perspective – a move away from damaging, cold static organ storage to the use of warm normothermic perfusion. The concept for warm preservation is one that has been borrowed from Nature, and it is only fitting that we go back to the wild for more 'tricks' to further improve warm organ stabilization. Current warm preservation strategies are designed to mimic natural conditions in the human body as closely as possible, but what if we could mimic these conditions while simultaneously inducing a reversible state of torpor that would further extend the viability window of donor organs? Indeed, the original driver for using cold organ storage was its ability to strongly reduce metabolic rate many‐fold when organs were cooled from 37 to 5 °C. Herein, we discuss the adaptations that allow warm hibernators such as bears and lemurs (fellow primates) to naturally depress their metabolic rate and retreat into states of suspended animation, and how these can be applied to improve organ transplant therapy. Can we look to Nature for instructions to induce torpor in human organs? This article discusses the possibilities. Abstract : Organ transplantation is moving away from 'perfuse, chill, pack in a cooler, and run'! Initial cold preservation strategies were borrowed from Nature, and it is only fitting that we go back to the wild for more tricks to extend donor organ viability. This article explores the use of metabolic rate depression adaptations of NOVEL hibernators to bolster new, warm, preservation.